Clinical significance and prognostic value of receptor conversion after neoadjuvant chemotherapy in breast cancer patients - He, Yang; Zhang, Jing; Chen, Hui; Zhou, Ying; Hong, Liping; Ma, Yue; Chen, Nannan; Zhao, Weipeng; Tong, Zhongsheng (Frontiers in Surgery, 2023)
The hormone receptor (HR) status and human epidermal growth hormone receptor 2 (HER2) status of patients with breast cancer may change following neoadjuvant chemotherapy (NAC). We retrospectively analyzed the clinical data of 294 patients with stage II/III breast cancer to evaluate the clinical significance and prognostic value of receptor transformation after NAC in breast cancer patients. Pathological complete response after NAC was achieved in 10.7% of patients. HR, estrogen receptor (ER), progesterone receptor (PR), HER2, and Ki-67 conversion rates were 9.2%, 6.5%, 13.0%, 4.4%, and 33.7%, respectively. Patients with stable HR (P = 0.01) and HER2 (P = 0.048) expression had more favorable overall survival (OS). Low or reduced Ki-67 expression was associated with better disease-free survival (DFS) (P < 0.001) and OS (P < 0.01). Multivariate analysis showed that the number of lymph nodes after NAC, HR conversion, and radiotherapy were independent prognostic factors for overall survival. HR conversion implied a higher risk of death [hazard ratio, 2.56 (95% confidence interval: 1.19–5.51); P = 0.016]. Patients with HR conversion after NAC who received endocrine therapy had better DFS (P = 0.674) and OS (P = 0.363) than those who did not receive endocrine therapy, even if the HR changed from positive to negative. In conclusion, pathological testing should be performed before and after NAC, and even patients with HR conversion after NAC might benefit from endocrine therapy.